Implementation Analysis on Society-Based Hospital Concept with Software-as-a-Service (SaaS) Technology - Yustim, Benny; ., . (International Journal of Engineering and Technology, 2018)
The high mortality rate of pregnant women in Indonesia due to the low monitoring of their health conditions needs to get special attention from all interested parties. Recording of the development of the health of pregnant women in the Cohort book at the Puskesmas or Clinic is currently only used as a routine when examining pregnant women and has not been used optimally. Data stored in the Cohort book can basically be used as an indicator of the health development of pregnant women, but technology is needed that can monitor and disseminate existing information so that relevant parties can use the information. The application of the concept of Society-Based Hospital, can be one solution for monitoring the condition of pregnant women so that action can be followed up. This concept involves hospitals in a particular area to reduce the limited resources of specialist doctors who are not owned by the Puskesmas or Clinic. The application of the RSBM concept and supported by existing technology, is expected to disseminate information to all relevant parties, so that it can provide rapid action, so as to reduce the high maternal and child mortality rates.Â